Analisis Komparasi Abnormal Return Dan Volume Perdagangan Saham Atas Pemberlakuan Peraturan Pemerintah Nomor 1 Tahun 2014 - Purba, Terkelin (JURNAL RISET BISNIS DAN MANAJEMEN, 2017)
The results showed during the study period (January 6 until January 20,2014) found the average - average abnormal return, where more abnormal return is positive which means the market is assessing the implementation of Regulation No. 1 of 2014 is good news. Nonetheless, there are significant differences in the average - average abnormal return before and after the implementation of Regulation No. 1 of 2014 which showed that the ban on the export of raw minerals would have no impact on the change in investor preference towards investment decisions. Statistical test results mean difference - Average Trading Volume Activity in the study period showed that there were no significant differences in the average Trading Volume Activity before and after the enactment of Regulation No. 1 of 2014. This condition showed no significant market reaction to the policy, so there was little decrease in the average - average trading volume of mining stocks after Regulation No. 1 of 2014 is enforcedKeywords: Abnormal return, Trading Volume activity, event study